Exploring how immigrant international medical graduates successfully manage complex sociocultural challenges - Marthyman, Azaria; Nimmon, Laura (Canadian Medical Education Journal, 2023)
Background: While immigrant international medical graduates (I-IMGs) contribute significantly to the physician workforce in North America, researchers have highlighted the myriad of ways sociocultural challenges can negatively impact their success. Conceptual understanding that unpacks the complex processes of how I-IMGs effectively manage sociocultural challenges is relatively sparse. In addressing this critical knowledge gap, this study explored how I-IMGs successfully manage sociocultural differences as postgraduate residents. Methods: We interviewed eleven I-IMGs from diverse backgrounds who are in training or recently trained in a distributed multi-site postgraduate medical training program in Canada. We used the lens of sociocultural learning theory to gain insights into the processes of how I-IMGs describe successful management of sociocultural challenges. Results: The overarching storyline of participants emphasized that their experiences were humbling as they grappled with inner struggles, emotions, and vulnerabilities while embracing the ambiguity of not knowing what was expected of them. The following dominant themes from their narratives encapsulate the salient processes for how I-IMGs conceptualize and successfully manage sociocultural challenges: 1) successfully navigating transitions; 2) resisting or altering elements of prior sociocultural norms while embracing the new; 3) living and being in community and having supportive social networks; 4) risk taking to self-advocate and actively seek help. Conclusion: Understanding the strengths and positive strategies for how I-IMGs interface with complex sociocultural challenges has application for medical training institutions. Our insights suggest the need for practical, effective, and continuous assistance within I-IMG training programs to better support future trainees dealing with sociocultural challenges.